The Effects of the PEM Fuel Cell Performance with the Waved Flow Channels - Yue-Tzu Yang; Kuo-Teng Tsai; Cha’o-Kuang Chen (Journal of Applied Mathematics)
The objective of this study is to use a new style of waved flow channel instead of the plane surface channel in the proton exchange membrane fuel cell (PEMFC). The velocity, concentration, and electrical performance with the waved flow channel in PEMFC are investigated by numerical simulations. The results show that the waved channel arises when the transport benefits through the porous layer and improves the performance of the PEMFC. This is because the waved flow channel enhances the forced convection and causes the more reactant gas flow into the gas diffusion layer (GDL). The performance which was compared to a conventional straight gas flow channel increases significantly with the small gap size when it is smaller than 0.5 in the waved flow channel. The performance is decreased at the high and low velocities as the force convection mechanism is weakened and the reactant gas supply is insufficient. The pressure drop is increased as the gap size becomes smaller, and the wave number decreases. (gap size) δ > 0.3 has a reasonable pressure drop. Consequently, compared to a conventional PEMFC, the waved flow channel improves approximately 30% of power density.